2021
DOI: 10.1111/nph.17574
|View full text |Cite
|
Sign up to set email alerts
|

Native plant species show evolutionary responses to invasion by Parthenium hysterophorus in an African savanna

Abstract: Invasive plant species often competitively displace native plant species but some populations of native plant species can evolve adaptation to competition from invasive plants and persist in invaded habitats. However, studies are lacking that examine how variation in abiotic conditions in invaded landscapes may affect fitness of native plants that have adapted to compete with invasive plants.I tested whether invasion by Parthenium hysterophorus in Nairobi National Park -Kenya may have selected for native plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 77 publications
3
12
0
Order By: Relevance
“…Nitrogen is often the most limiting nutrient for plant growth in most ecosystems, which is very important for fast-growing plants, especially invasive plants ( Uddin and Robinson, 2018 ; Zhang et al., 2022 ). Invasive plants have more advantages in N allocation than native plants, which will promote the response of invasive plants to the N environment ( Hu et al., 2022 ; Oduor, 2022 ). To explore the response of S. canadensis under a N environment, transcriptome analysis was performed among different N deposition level environments.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen is often the most limiting nutrient for plant growth in most ecosystems, which is very important for fast-growing plants, especially invasive plants ( Uddin and Robinson, 2018 ; Zhang et al., 2022 ). Invasive plants have more advantages in N allocation than native plants, which will promote the response of invasive plants to the N environment ( Hu et al., 2022 ; Oduor, 2022 ). To explore the response of S. canadensis under a N environment, transcriptome analysis was performed among different N deposition level environments.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible explanation for the present finding would be that the alien species have developed adaptations to the allelochemicals produced by the native communities, due to the relatively long history ( Table S1 ) of co-occurrence with the native plant species in China. Studies have shown that native plant species can adapt to competition from invasive alien plant species (Callaway et al 2005; Oduor 2013, 2022) but the opposite is also likely to occur as some alien species may develop adaptations to native plant species. The present results corroborate those of Zhang et al (2021), who conducted a meta-analysis based on 792 pairwise allelopathic effects of native plants on naturalized alien plants and found that such allelopathic effect is overall neutral (the net effect of the allelopathy is not significantly different from zero).…”
Section: Discussionmentioning
confidence: 99%
“…And this study only inferred from the phenotypic traits that the co-evolutionary history of competitors and G. quadriradiata in uenced the relationship between them. However, phenotypic trait expression is in uenced by heritable genetic and epigenetic factors (Oduor 2022). Overall, future studies need to be carried out on co-evolution history of other invasive plants and competitors in more habitats, and multi-generation growth of test plants can be used to test whether trait differences persist over time, and the genetic mechanism should be further explored.…”
Section: The Effect Of Competitors With Different Shared Co-evolution...mentioning
confidence: 99%
“…Genetic variation in traits that are resistant to strong competition from invasive plant species may enable native plants to evolve to adapt to invasive plant species (Oduor 2013;Strauss et al 2006). For example, a study on the African savannas suggests that Parthenium hysterophorus invasions may have exerted selective pressure on native plants, leading to the differentiation of growth and reproductive traits between invasive and adjacent noninvasive habitats(Oduor 2022). And it has been found that native plants may evolve a tolerance reducing the negative effects of invasive plants allelopathic compounds…”
mentioning
confidence: 99%